Multi-soliton generation using a micro ring resonator system for dwdm based soliton communication - Pornsuwancharoen, N.; Dunmeekaew, U.; Yupapin, P. P. (My University, 2009)
We propose a new optical system that can be used to form the multi soliton pulses within the micro ring resonators. The system consists of two micro ring resonators and an add/drop multiplexer that can be integrated into a single system. The large bandwidth signal is generated by using a soliton pulse propagating in a Kerr type nonlinear medium. The tuned soliton pulses in either spatial or temporal modes are obtained by using the add/drop multiplexer. Results obtained have shown that the multi soliton pulses can be localized coherently within the micro ring waveguide. This is shown that the generation of the multi soliton pulses within the micro ring resonator is achieved, which is available for long distance communication with dense wavelength division multiplexing (DWDM). A significant increase in channel number and spacing is obtained, and the large free spectrum range (FSR) of 600 pm is achieved. © 2009 Wiley Periodicals, Inc.
Keywords: DWDM; Localized soliton; Multi soliton; Optical filter; Optical memory